Portrait - Nancy, Jean-Luc (Book collections on Project MUSE., 2018)
This work examines the practice of portraits as a way in to grasping the paradoxes of subjectivity. The text is written from the perspective that the portrait is suspended between likeness and strangeness, identity and distance, representation and presentation, exactitude and forcefulness. It can identify an individual, but it can also express the dynamics by means of which its subject advances and withdraws. It consists of two extended essays written a decade apart but in close conversation, in which the author considers the range of aspirations articulated by the portrait. Heavily illustrated, it includes a newly written preface bringing the two essays together and a substantial introduction, which places the author's work within the range of thinking of aesthetics and the subject, from religion, to aesthetics, to psychoanalysis.